2018
DOI: 10.1111/jpn.12993
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary ginseng polysaccharide supplementation on porcine milk‐derived esRNAs involved in the host immune responses

Abstract: Ginseng polysaccharides (GPS) have been well known as an immune modulator. This study was conducted to investigate the effects of dietary supplemental GPS on the immune responses involved in sow’s milk‐derived exosomal shuttle RNAs (esRNAs) using RNA‐Seq and miRNA‐Seq. Of the 213 identified miRNA types, a total of 26 conserved miRNAs were differently expressed in response to GPS supplementation, including 10 up‐regulated and 16 down‐regulated miRNAs in GPS feeding group. In addition, exosomal transcriptome ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Moreover, reports about changes in the exosome composition induced by diet are currently limited to the lipid and the miRNA cargo: Kumar et al (2021) found that feeding a high-fat diet altered the lipid composition of exosomes, and further administration of exosomes isolated from the feces of obese mice led to insulin resistance in lean mice. In addition, modulation of microRNA present in milk exosomes was reported upon dietary supplementation of ginseng polysaccharides in sows (SUN et al, 2019) and by replacing alfalfa hay with whole cottonseed in the diet of dairy cows . To the best of our knowledge, our study is the first to address changes induced by the diet in the milk exosome proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reports about changes in the exosome composition induced by diet are currently limited to the lipid and the miRNA cargo: Kumar et al (2021) found that feeding a high-fat diet altered the lipid composition of exosomes, and further administration of exosomes isolated from the feces of obese mice led to insulin resistance in lean mice. In addition, modulation of microRNA present in milk exosomes was reported upon dietary supplementation of ginseng polysaccharides in sows (SUN et al, 2019) and by replacing alfalfa hay with whole cottonseed in the diet of dairy cows . To the best of our knowledge, our study is the first to address changes induced by the diet in the milk exosome proteins.…”
Section: Discussionmentioning
confidence: 99%
“…( 3) maternal diet or nutrition: Animal studies showed that diet changed the expression of miRNAs in milk-derived EVs. Adding ginseng polysaccharides as immunomodulators to the diet of sows altered the expression of immune-related miRNAs in porcine milkderived exosomes, influencing offspring development (Sun et al, 2019). Quan et al (2020) replaced a portion of original alfalfa hay in the feed of dairy cows with whole cottonseeds and soybean hulls.…”
Section: Factors Influencing the Content And Biological Activity Of Milk-derived Evsmentioning
confidence: 99%
“…The majority of milk microRNAs are encapsulated within EVs that ensure their stability against harsh conditions (Benmoussa et al., , ; van Herwijnen et al., ; Wang, ). Milk microRNAs can be specifically loaded into different kinds of EVs (Shu, Chiang, Zempleni, & Cui, ; Villarroya‐Beltri et al., ), leading to specific microRNA profiles between EV subsets (Benmoussa et al., ; Chiang, Shu, Zempleni, & Cui, ; Manca et al., ; Shu et al., ), and this loading process can be influenced by the environment, by dietary habits (Paredes et al., ; Xi et al., ) or food supplementation as observed for dietary ginseng polysaccharide supplementation on porcine milk microRNAs (Sun et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%